Analysis of Trace Elements in Human Brain: Its Aim, Methods, and Concentration Levels - Grochowski, Cezary; Blicharska, Eliza; Krukow, Paweł; Jonak, Kamil; Maciejewski, Marcin; Szczepanek, Dariusz; Jonak, Katarzyna; Flieger, Jolanta; Maciejewski, Ryszard (Frontiers in Chemistry, 2019)
Trace elements play a crucial role in many biochemical processes, mainly as components of vitamins and enzymes. Although small amounts of metal ions have protective properties, excess metal levels result in oxidative injury, so metal ion homeostasis is crucial for proper functioning of the brain.. The changes of their level in the brain has been proven to be a risk factor for Alzheimer, Parkinson and Huntington disease, and amyotrophic lateral sclerosis. Therefore, it is currently an important application of various analytical methods. This review covers most important of them: inductively coupled ground mass spectrometry (ICP-MS), flame-induced atomic absorption spectrometry (FAAS), electrothermal atomic absorption spectrometry (GFAAS), optical emission spectrometry with excitation in inductively coupled plasma (ICP-OES), X-ray fluorescence spectrometry (XRF) and neutron activation analysis (NAA). A summary of concentration values found by different research groups is also given for the reader’s reference.